La práctica danzaria del Bambuco fiestero en candidatas y parejos oficiales en el marco del Festival y Reinado Nacional del San Pedro en el Espinal, Tolima en pos-pandemia, 2022. (2023)
This thesis systematizes the artistic experience to the current state of the tradition - EAPEAT- within the framework of the National Festival of San Pedro in Espinal in 2022, after two years in which it was not scheduled due to the COVID 19 pandemic, through the description and examination of the experiences, feelings of two candidates and two official partners for the National Reign of San Pedro in Espinal 2022 in a post-pandemic context, to identify how this influenced the current state of the dance tradition practice of the bambuco fiestero of San Pedro in Espinal, to reflect on the impact of the health emergency on this dance tradition festival.